Kemampuan Berpikir Kritis Mahasiswa pada Materi Aplikasi Persamaan Diferensial Orde Satu Masalah Peluruhan - Arfatin Nurrahmah; Lasia Agustina; Nurhayati Nurhayati (Institut Agama Islam Negeri Curup, 2022)
This article aims to describe students' critical thinking ability in the application material of one-order differential equations, especially decay problems. This study used a qualitative descriptive method, three students of the sixth semester in Universitas Indraprasta PGRI were selected as research subjects. The instruments used in the study are tests, interview guidelines as well as researchers as key instruments. Data analysis techniques are carried out through data reduction, which is continued the presentation of data, as well as the withdrawal of conclusions/verification. Data validity test is done through triangulation technique. The results showed that S1 with high critical thinking ability, fulfilling all indicators, namely interpreting problems, analyzing solutions from problems, implementing solutions, evaluating solutions, and inferring results. S2 with medium critical thinking ability is meeting two indicators, namely interpreting problems and analyzing solutions, and S3 with low critical thinking ability has not met all the indicators.